Analisis kemampuan komunikasi matematis pada pembelajaran Think Pair Share (TPS) berbantu komik matematika - ana, susi; Negara, Hasan Sastra; Wati, Netri (Universitas PGRI Semarang, 2019)
The purpose of this study was to find out whether the TPS Learning Model Helped by Mathematical Comics had an effect on the mathematical communication of class VII of Bandar Lampung Middle School 14. Based on data analysis and hypothesis testing that has been carried out that the implementation of the Mathematical comic-assisted TPS Learning Model to the class Experiments on Quadrilateral material has an influence on students' Mathematical Communication skills. This can be seen from the results of calculations using the one sample T-test of tcount (2.870) t table (, 0452). This indicates that tcount ttable so Ho is rejected in other words Ha is accepted, so there are influences of TPS learning models aided by mathematical comics . In qualitative analysis for high-ability students able to complete 3 stages including; (1) Written Text (2) Drawing (3) Mathematical Expression for ability students who are only completing 2 stages include (1) Written (2) Mathematical Expression about mathematical communication, while for low ability students only 1 stage (1) Written Text.